Thermomechanical and gas transport behavior of silica-doped polymer blend nanocomposites. Issue 2 (14th April 2021) - Patel, Avani; Acharya, Naveen Kumar
Abstract : Blending of polymers enhances the transport rate of gases due to cross-linking of polymer chains. Nanofillers dispersed into a single polymer matrix also tend to modify the transport behavior. Polymer blend nanocomposites show changes in their thermomechanical and gas transport properties. Blending plays a vital role in improving gas permeation. Silica nanoparticles are used as filler with a polycarbonate and polysulfone polymer matrix. Membranes were prepared using the solution-casting method, and uniform dispersion of silica nanoparticles was obtained by sonication. A gas permeability test for hydrogen (H2 ) and carbon dioxide (CO2 ) was carried at 30 pounds per square inch (207 kPa) constant upstream pressure at room temperature using the constant pressure/variable volume method. Oxygen permeability was determined from the oxygen transmission rate using the differential pressure method. Characterization of thermomechanical properties was carried out using differential scanning calorimetry and dynamic mechanical analysis.